PERSEPSI DAN SIKAP MASYARAKAT TERHADAP PENGELOLAAN HUTAN ADAT (Studi Kasus di Kasepuhan Pasir Eurih, Desa Sindanglaya, Kecamatan Sobang, Kabupaten Lebak, Provinsi Banten) - Pratiwi, Ruhestiana; Nitibaskara, Tb Unu; Salampessy, Messalina L (Universitas Nusa Bangsa, 2018)
Perception and Behavior of Indigenous People to Indigenous Forest Management are essential to maintaining the sustainability of forest functions. The aims of this study were to describe and explain the perception and behavior of indigenous peoples to indigenous forest management. The Data were conducted by interview and observation which analyzed by using descriptive analysis. The results showed that the indigenous people of Kasepuhan Pasir Eurih had a high perception of the community with a percentage of 90% - 93.34% indicated by a good understanding that their lives depend on indigenous forest resources and want to sustain the resources. The number of community’s dependence on indigenous forest ecosystems is very high, especially in sustaining its economic life. While high behavior with percentage is about 73.33% - 93.33% which means that the community is very understanding of conservation activities in indigenous forest management.